Рreparation of bachelor translators in the institutions of higher education of China - Yanshi, Liu; Kravchenko, Н. (Problems of Engineer-Pedagogical Education, 2021)
The article deals with the training of bachelor translators in higher education institutions in China. The system of training qualified personnel in the specialty of a translator in the context of educational institutions has been studied by many scientists from different countries. Basically, the studies drew attention to the problems of teaching students, providing for the creation of certain conditions for obtaining the necessary knowledge that guide the professional development of the student. The authors found that the preparation of bachelors in interpretation and translation in institutions of higher education in China is closely linked to the national strategy for its development. The article separately emphasizes that teaching students to translate from foreign languages, in colleges and universities, must adhere to three basic conditions: compliance with translation traditions; the availability of training programs for a translator-bachelor, corresponding to professional characteristics; the presence of a qualified team of professional teachers. The authors of the article also note that professional standards of student preparation are based on National Standards. Professional standards impose certain requirements for the training of bachelor translators, namely: requirements for the quality of training; knowledge requirements; skill requirements; requirements for the development of core training courses. The work focuses on the analysis of the content of training standards for bachelor translators and the directions of its implementation in the educational programs of colleges and universities in Sichuan in China. This gave the authors the opportunity to draw the following conclusions: the objectives of training bachelortranslators are mainly related to the corresponding description of “training requirements”, which covers three aspects: positioning of bachelor-translators, requirements for target skills, and orientation toward future professional employment. It should be noted that a positive aspect in the training of future translators at Chinese universities, in our opinion, is a clear orientation of the learning process to date and future practical tasks that students will meet in their professional activities after graduation